Islam, Tourism Development and Religious Behavior: Analysis of the Implementation of Tourism Development Policy at the PB VI Selo-Boyolali Intersection - Mahmudi, Imam; Mufid, Moh. (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
The development of the tourism industry is the agenda of the Boyolali Regency government to encourage economic development and to increase regional PAD. The aim of industrial development is to encourage progress in the economic, social, cultural and religious fields of society. Currently, in the VIllage of Samiran Selo-Boyolali, a tourism object at the Simpang PB VI Selo-Boyolali has been built. This study will analyze the impact of implementing tourism development policies on people's religious behaVIor. This study uses a qualitative descriptive method. Then in the data collection process using the method of observation, interVIews, and documentation. The implementation of the Simpang PB VI tourism development policy has an impact on two things, namely positive and negative impacts. The positive impact of tourism development on people's religious behaVIor is in the form of: (a). Increasing public knowledge about the modern economic system. (b). Strengthening the economy and religion of society. (b). The opening of employment opportunities for the community so that they are able to send their children to Islamic boarding schools. (c). Minimizing behaVIor that is not in accordance with religious norms. The negative impacts of tourism are: (a). Westernized lifestyle (lifestyle) that is not in accordance with religious teachings. (b). Reducing the comfort of the community in carrying out makhdzoh and ghoiru makhdzoh worship. (c). Changes in youth behaVIor that are not in accordance with religious and cultural teachings.